Increased stathmin1 expression in the dentate gyrus of mice causes abnormal axonal arborizations. - Kohei Yamada (PLoS ONE, 2010)
Pituitary adenylate cyclase-activating polypeptide (PACAP) is involved in multiple brain functions. To clarify the cause of abnormal behavior in PACAP deficient-mice, we attempted the identification of genes whose expression was altered in the dentate gyrus of PACAP-deficient mice using the differential display method. Expression of stathmin1 was up-regulated in the dentate gyrus at both the mRNA and protein levels. PACAP stimulation inhibited stathmin1 expression in PC12 cells, while increased stathmin1expression in neurons of the subgranular zone and in primary cultured hippocampal neurons induced abnormal arborization of axons. We also investigated the pathways involved in PACAP deficiency. Ascl1 binds to E10 box of the stathmin1 promoter and increases stathmin1 expression. Inhibitory bHLH proteins (Hes1 and Id3) were rapidly up-regulated by PACAP stimulation, and Hes1 could suppress Ascl1 expression and Id3 could inhibit Ascl1 signaling. We also detected an increase of stathmin1 expression in the brains of schizophrenic patients. These results suggest that up-regulation of stathmin1 in the dentate gyrus, secondary to PACAP deficiency, may create abnormal neuronal circuits that cause abnormal behavior.